Imperial Emotions : Cultural Responses to Myths of Empire in Fin-De-Siècle Spain. - Krauel, Javier. (Contemporary Hispanic and Lusophone Cultures Series, 2013)
A ground-breaking work that considers myths of the Spanish empire from the perspective of cultural responses to its demise.